Where’s the best supermarket deal? Female Southern Rockhopper Penguins (Eudyptes chrysocome) show variable foraging areas during the guard stage at Isla de los Estados, Argentina - Rosciano, Natalia Gimena (2021)
Understanding the spatial distribution of seabirds contributes to comprehending their ecological requirements and dispersion patterns. We studied the at-sea distribution of female Southern Rockhopper Penguins (Eudyptes chrysocome (J.R. Forster, 1781)) at Isla de los Estados colony during the early chick-rearing period. We used a clustering analysis approach to identify different groups according to the foraging trip (tracking and diving data from GPS and temperature and depth data loggers) and diet (d15N composition on blood samples) characteristics. Foraging trips differed in duration, location, and dive depths explored. Females in clusters 1 and 3 traveled longer distances and in opposite directions (36.3 6 21.3 and 40.3 6 14.0 km, respectively). Females in cluster 2 fed closer to the colony (16.8 6 7.8 km). Dives occurred in pelagic habitats. Higher d15N values suggested a greater proportion of fish (e.g., the Fuegian sprat, Sprattus fuegensis (Jenyns, 1842)) consumption in the northern foraging areas (cluster 1). The variability observed in the spatial distribution suggests flexibility in the foraging behavior of Southern Rockhopper Penguins and availability of adequate foraging areas within the colony range during the early chick-rearing period, both important features for Southern Rockhopper Penguin population. These results contribute to understanding the use of the Southern Ocean by marine mesopredators and top predators and to the marine spatial planning in the area.